Variation in Spirometric Parameters among Type 2 Diabetes Mellitus Patients and their Association with Duration of Disease and Glycemic Control - S Muthukumar; V Roselin; N Prabhu (Asian Journal of Medical Research, 2022)
Background: Pulmonary function test using spirometry is a simple cost effective method to identify the lung function impairment among type 2 Diabetes Mellitus (DM) patients. Even though pulmonary function is impaired among diabetics there are no signs and symptoms of reduced lung function. Hence this study was aimed to find out the pulmonary function in DM patients, to compare the spirometry parameters of Diabetic patients with non-diabetics and correlate spirometry abnormalities with duration of diabetes and HbA1C. Subjects and Methods: A Cross sectional comparative study done among DM patients (Group 1) and non diabetics (Group 2), in a teaching hospital from June 2018 to January 2019. There were 106 study subjects in each group. All the 212 participants were subjected to spirometry and the readings were interpreted as normal, obstructive, restrictive or mixed pattern. Both the groups were compared for spiromertric observations. Pulmonary function in group 1 was analyzed based on duration of diabetes and HbA1C. Mean and SD was calculated. p value was calculated using chi-square and T-test. Results: The mean age of patients with DM and non-diabetes was 53.58 and 51.27 years respectively. The spirometry inference among DM patients was 30.2%, 20.8%, 18.9% and 30.1% as normal, restrictive, obstructive and mixed pattern respectively. p value was found to be statistically significant for FVC, FEV1 and PEFR and FEF25-75%. Conclusion : Spirometry can be used as a tool to find out the pulmonary function among diabetic patients earlier and to reduce morbidities due to respiratory complications.